Pengaruh Pengetahuan Program Komunikasi City Branding World’s City of Batik Kota Pekalongan Terhadap Persepsi Citra Kota dan Minat Berkunjung Wisatawan - Kukuh Mujiono; S. Rouli Manalu (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
This study aims to analyze the influence of knowlegde of World’s City of Batik’s city branding communication program on perceptions of city image and tourist visiting interest in Pekalongan city. Pekalongan City created a city branding called “World’s City of Batik” in 2011. Yet, within five years (2012-2016) the number of city tourist visits fluctuated and event tanded to decline. Based on hypothesis testing carried out using simple regression analysis, the results of this study shows that there is a significant effect of knowlegde of city branding communication program on perceptions of city image (0,000<0,05) with a determination value of 0,369, there is a significant effect of knowledge of city branding communication program on tourist visiting interest (0,000<0,05) with a determination value of 0,436, and there is a significant effect of perceptions of city image on tourist interest (0,0005<0,05) with a determination value of 0,462. Although there are a significant effect, there are other factors outside of this study that have a greater effect. That is because the constant values of the influence of the knowlegde of the city branding communication program on the perceptions of city image (41,086) and the influence of the knowlegde of the city branding communication program on tourist interest (20,852) are far greater than their coefficient values (0,761 and 0,580). Except the constant value (3,133) and coeffisien value (0,535) of the influence of the perceptions of city image on tourist interest is not too far apart. Therefore, further research can be carried out to examine other factors.